2013
DOI: 10.1007/s11356-013-2217-5
|View full text |Cite
|
Sign up to set email alerts
|

A review of strategies to monitor water and sediment quality for a sustainability assessment of marine environment

Abstract: The basic aim of this work is (1) to review and present practically operational requirements for a sustainability assessment of marine environment, such as describing the monitoring process, research approaches, objectives, guidelines, and indicators and (2) to illustrate how physico-chemical and biological indicators can be practically applied, to assess water and sediment quality in marine and coastal environment. These indicators should meet defined criteria for practical usefulness, e.g. they should be sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 102 publications
0
20
0
1
Order By: Relevance
“…Further research revealed significant differences in the sources and concentration of PAHs in sediment samples of near-shore vs. offshore areas. PAH concentrations in sediment samples collected from near-shore sites (city hinterland) were greater than the PAH concentrations in offshore areas [11], [30], [37], [38], [39]. This implies that PAH concentrations in near-shore areas are influenced by lateral transport, such as run-off and the transportation of water due to daily rainfall [12], [40].…”
Section: Resultsmentioning
confidence: 99%
“…Further research revealed significant differences in the sources and concentration of PAHs in sediment samples of near-shore vs. offshore areas. PAH concentrations in sediment samples collected from near-shore sites (city hinterland) were greater than the PAH concentrations in offshore areas [11], [30], [37], [38], [39]. This implies that PAH concentrations in near-shore areas are influenced by lateral transport, such as run-off and the transportation of water due to daily rainfall [12], [40].…”
Section: Resultsmentioning
confidence: 99%
“…Biodiversity monitoring is largely used for the environmental impact assessment of anthropogenic activities. According to tradition, in marine ecosystems, such impacts are assessed through the inventory of benthic macro‐invertebrates, which involve the sorting and the morphotaxonomic identification of thousands of specimens for a single site (Borja, Ranasinghe, & Weisberg, ; Tavakoly Sany, Hashim, Rezayi, Salleh, & Safari, ). Identified taxa are being ascribed to ecological weights that are used to calculate biotic indices (BIs), such as AMBI (Borja, Franco, & Pérez, ), ISI (Rygg, ), NSI or NQI1 (Rygg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sediments are good hosts of highly toxic pollutants from natural and anthropogenic sources [74] and have been reported as the biggest sink and major reservoir for heavy metals [75][76][77][78][79][80][81][82]. Sediments enhance accumulation of heavy metals in benthic invertebrates, thereby transferring them to higher levels of the food chain [83][84][85][86][87].…”
Section: Superficial Sedimentsmentioning
confidence: 99%